Traumatic brain injury, driver aggression and motor vehicle collisions in Canadian adults. (August 2015) - Ilie, Gabriela; Mann, Robert E.; Ialomiteanu, Anca; Adlaf, Edward M.; Hamilton, Hayley; Wickens, Christine M.; Asbridge, Mark; Rehm, Jürgen; Cusimano, Michael D.
Highlights: This study examined the relationships between brain injury, road aggression and collisions. Results indicate that a large proportion of adult drivers have a history of brain injuries. A disproportion number of traffic safety problems may stem from drivers' brain injuries. Improved screening and rehabilitation are needed for drivers with a history of brain injuries. Abstract: Objective: This study examines the associations between lifetime traumatic brain injury (TBI), driver aggression, and motor vehicle collisions among a population sample of adults who reside in the province of Ontario, Canada. Method: A cross-sectional sample of 3993 Ontario adults, aged 18–97 were surveyed by telephone in 2011 and 2012 as part of Center for Addiction and Mental Health's ongoing representative survey of adult mental health and substance use in Canada. TBI was defined as trauma to the head that resulted in loss of consciousness for at least five minutes or overnight hospitalization. Results: An estimated 91% (95% CI: 90.0, 91.9) of individuals in this sample held a valid Ontario driver's license at the time of testing. Among those, 16.7% reported a history of lifetime TBI and 83.3% reported no TBI. The prevalence of TBI was higher among men than women. Relative to licensed adults without TBI, adults with a history of TBI had significantly higher odds of engaging in serious driver aggression in the past 12 months, such as making threats to hurt another driver, passenger or their vehicle (AOR = 4.39). These individuals also reported significantly higher odds (AOR = 1.74) of being involved in a motor vehicle collision that resulted in hurting themselves, their passenger(s) or their vehicle. Conclusion: This is the first population-based study to demonstrate a relationship between a history of TBI and higher rates of serious driver aggression and collision involvement. Given the large proportion of adult drivers with a history of TBI, these individuals may account for a disproportion burden of all traffic safety problems. Whether the increased road safety risk of adults with a history of TBI is reflective of neurocognitive deficits or is merely evidence of a cluster of unsafe activities produced by a higher risk lifestyles requires further research attention.